Hubungan Kepuasan Kerja dengan Komitmen Organisasi Pada Guru di SMA Negeri 1 Halmahera Utara - Heni Kristiana Masahe (Peneliti.net, 2021)
Commitment is needed in educational organizations because a teacher who has a high commitment to the school organization will tend to have a professional attitude and uphold the agreed values. One of the factors that influence commitment is job satisfaction. This study aims to determine the relationship between job satisfaction and commitment. Researchers used quantitative methods to achieve the objectives of this study. The research subjects used in this study were teachers of SMAN 1 Halmahera Utara, totaling 35 teachers. The sampling technique used is Simple Random Sampling. The results of data analysis showed a correlation value (r) of 0.821 with a significance (p) = 0.000 (p <0.05). This shows that there is a very significant positive relationship between job satisfaction and commitment.